ANALISIS PELAKSANAAN PENDAMPINGAN AKREDITASI PUSKESMAS PADA KELOMPOK KERJA ADMINISTRASI DAN MANAJEMEN DI KABUPATEN PEMALANG - Hendra Teguh Setiawan; Sutopo Patria Jati; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Accreditation assistance is an activity that aims to facilitate puskesmas in order to improve quality and service performance in accordance with standard and accreditation instrument of puskesmas. The score result at 14 puskesmas targeted for assistance in 2016 and 2017, most are accredited basic and showed the lowest score in the administrative and management working group. The objective of this study is to analyze the implementation of puskesmas accreditation in the administration and management working group in Pemalang. This study uses qualitative method with descriptive approach. The data was collected through in-depth interviews to two key informants and three triangulation informants. The results showed that in general the implementation of puskesmas accreditation assistance in Pemalang has been running, but if it is seen the quality of the implementation was still less than the maximum. There were still members of assistant team who have not been trained and have a competence assistant certificate; the activity planning did not detail the whole of the assistance activities but only focused on budget planning and scheduling activities; the implementation of accreditation assistance activities was limited for pre accredited certification assistance. The advice given is to facilitate education and training of untrained team members, making planning activities based on evidence data freom the result of self assessment so that assisstenace more directed; create a clear monitoring and evaluation schedule related to the implementation of accreditation assistance.